Hubungan Antara Kecerdasan Emosi dengan Agresivitas Remaja - Djuwariyah Djuwariyah (Psikologika: Jurnal Pemikiran dan Penelitian Psikologi, 2002)
This research was aimed at determining the relationship between emotional intelligence and aggressiveness. The subject of the research were 15o first and secondyears Junior High School students of  SLTP Muhammadiyah 3 Kolombo, Depok Yogyakarta in 1999/2000 school year. The data collection was done using the questionnaire method for the scale of emotional intellligence, whereas the scale of aggressiveness in the narrative form (vignette) to expressed of the aggressiveness. The relationship between emotional intelligence and aggressiveness used Product Moment analysis. The result of correlation analysis was –0,402 (p=0,000). This means that the higher the emotional intelligence, the lower the aggressiveness. Key Word : emotional intelegence, aggressiveness